Update on the Role of Cannabinoid Receptors after Ischemic Stroke - Luciano S. A. Capettini; Silvia Q. Savergnini; Rafaela F. da Silva; Nikos Stergiopulos; Robson A. S. Santos; François Mach; Fabrizio Montecucco (Mediators of Inflammation)
Cannabinoids are considered as key mediators in the pathophysiology of inflammatory diseases, including atherosclerosis. In particular, they have been shown to reduce the ischemic injury after acute cardiovascular events, such as acute myocardial infarction and ischemic stroke. These protective and anti-inflammatory properties on peripheral tissues and circulating inflammatory have been demonstrated to involve their binding with both selective cannabinoid type 1 (CB1) and type 2 (CB2) transmembrane receptors. On the other hands, the recent discoveries of novel different classes of cannabinoids and receptors have increased the complexity of this system in atherosclerosis. Although only preliminary data have been reported on the activities of novel cannabinoid receptors, several studies have already investigated the role of CB1 and CB2 receptors in ischemic stroke. While CB1 receptor activation has been shown to directly reduce atherosclerotic plaque inflammation, controversial data have been shown on neurotransmission and neuroprotection after stroke. Given its potent anti-inflammatory activities on circulating leukocytes, the CB2 activation has been proven to produce protective effects against acute poststroke inflammation. In this paper, we will update evidence on different cannabinoid-triggered avenues to reduce inflammation and neuronal injury in acute ischemic stroke.